ALPPS Procedure for Extended Liver Resections: A Single Centre Experience and a Systematic Review. - Marco Vivarelli; Paolo Vincenzi; Roberto Montalti; Giammarco Fava; Marcello Tavio; Martina Coletta; Andrea Vecchi; Daniele Nicolini; Andrea Agostini; Emad Ali Ahmed; Andrea Giovagnoni; Federico Mocchegiani (PLoS ONE)
Aim To report a single-centre experience with the novel Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS) technique and systematically review the related literature. Methods Since January 2013, patients with extended primary or secondary liver tumors whose future liver remnant (FLR) was considered too small to allow hepatic resection were prospectively assessed for the ALPPS procedure. A systematic literature search was performed using PubMed, Scopus and the Cochrane Library Central. Results Until July 2014 ALPPS was completed in 9 patients whose mean age was 60 ± 8 years. Indications for surgical resection were metastases from colorectal cancer in 3 cases, perihilar cholangiocarcinoma in 3 cases, intrahepatic cholangiocarcinoma in 2 cases and hepatocellular carcinoma without chronic liver disease in 1 case. The calculated FLR volume was 289 ± 122 mL (21.1 ± 5.5%) before ALPPS-1 and 528 ± 121 mL (32.2 ± 5.7%) before ALLPS-2 (p < 0.001). The increase in FLR between the two procedures was 96 ± 47% (range: 24-160%, p < 0.001). Additional interventions were performed in 4 cases: 3 patients underwent Roux-en-Y hepaticojejunostomy, and one case underwent wedge resection of a residual tumor in the FLR. The average time between the first and second step of the procedure was 10.8 ± 2.9 days. The average hospital stay was 24.1 ± 13.3 days. There was 1 postoperative death due to hepatic failure in the oldest patient of this series who had a perihilar cholangiocarcinoma and concomitant liver fibrosis; 11 complications occurred in 6 patients, 4 of whom had grade III or above disease. After a mean follow-up of 17.1 ± 8.5 months, the overall survival was 89% at 3-6 and 12 months. The recurrence-free survival was 100%, 87.5% and 75% at 3-6-12 months respectively. The literature search yielded 148 articles, of which 22 articles published between 2012 and 2015 were included in this systematic review. Conclusion The ALPPS technique effectively increased the resectability of otherwise inoperable liver tumors. The postoperative morbidity in our series was high in accordance with the data from the systematic review. Age, liver fibrosis and presence of biliary stenting were predisposing factors for postoperative morbidity and mortality.